ANALISIS USAHATANI DAN KETERPADUAN PASAR PADA SISTEM PEMASARAN BAWANG MERAH DI KABUPATEN BENER MERIAH - Akhmad Baihaqi; Irwan Irwan; Romano Romano (Jurnal Agrisep, 2016)
This research aim to analyze farming system and integrity of market between market center consumer market and producer, and also to study price om parmer and marketing margin Method which is used in this research is survey method. Result of research show onion farmer obtain get 37 percent profit. Onion marketing system have walked relative goodness. This matter of indication with advantage of which can obtained by merchant and farmer and also the existence of real integration among market, while have commodity price it fluctuation to consumer storey level non because of do not the nun of system marketing of onion by condition of offer in producer storey level. This situation is strenghtened with result of research, related of market where there is negative correlation between wide of price and crop in producer storey level.